Toward Ethical Educational Management: Integrating Human And Financial Resource Practices With Islamic Leadership Principles At SMAN 1 Sampanahan - Sutrisno; Rahmani Hafizi; Suyoto; Rahmadi; Suriansyah; Aslamiah (IJGIE (International Journal of Graduate of Islamic Education), 2026)
The management of human and financial resources at SMAN 1 Sampanahan faces major challenges in improving educational quality amid budget constraints, technological advancement, and the growing demand for qualified educators. The effectiveness of human resource management and transparency in financial governance are crucial in achieving high-quality and accountable education. This study aims to examine the practices of human and financial resource management at SMAN 1 Sampanahan and analyze their impact on educational quality and achievement. Using a qualitative case study design, data were collected through in-depth interviews, direct observation, and document analysis, then analyzed thematically. The findings reveal that inclusive leadership by the principal, teacher involvement in decision-making, and continuous professional development have contributed to a collaborative work culture and improved student performance. Furthermore, transparent and accountable financial management practices have strengthened community trust and enhanced parental participation. The optimal synergy between human and financial resource management serves as a key factor in fostering an excellent and adaptive educational environment